Familial Clustering of Unexplained Transient Respiratory Distress in 12 Newborns from Three Unrelated Families Suggests an Autosomal-Recessive Inheritance. (2007) - Guala, Andrea; Carrera, Paola; Pastore, Guido; Somaschini, Marco; Ancora, Gina; Faldella, Giacomo; De Filippi, Paolo; Ferrero, Federica; Guarino, Roberta; Danesino, Cesare
Abstract : We report on 12 near-term babies from three families in which an unexplained transient respiratory distress was observed. No known risk factor was present in any family and no sequelae were recorded at follow-up. The most common causes of respiratory distress at birth are Neonatal Respiratory Distress Syndrome (NRD) and Transient Tachypnea of the Newborn (TTN), and their cumulative incidence is estimated to be about 2%. Genetic factors have been identified in NRD (surfactant genes) or suggested for TTN (genes affecting lung liquid clearance). Survivors from NRD may develop clinically relevant sequelae, while TTN does not cause any problem later in life. Our cases do not immediately fit NRD or TTN, while familial recurrence suggests the existence of a previously unreported subgroup on patients with respiratory distress for which autosomal-recessive inheritance is likely.